2020
DOI: 10.1111/dme.14408
|View full text |Cite
|
Sign up to set email alerts
|

Rates, determinants and success of implementing deprescribing in people with type 2 diabetes: A scoping review

Abstract: Background Individualizing goals for people with type 2 diabetes may result in deintensification of medication, but a comprehensive picture of deprescribing practices is lacking. Aims To conduct a scoping review in order to assess the rates, determinants and success of implementing deprescribing of glucose‐, blood pressure‐ or lipid‐lowering medications in people with diabetes. Methods A systematic search on MEDLINE and Embase between January 2007 and January 2019 was carried out for deprescribing studies amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 44 publications
(198 reference statements)
3
25
0
2
Order By: Relevance
“…Deprescribing comprises the systematic reduction or withdrawal of medication that may cause harm or no longer contributes to an individuals' health status [13,14]. Deprescribing of glucose-lowering medication in patients with comorbidity, frailty, hypoglycemic risk, or a limited life expectancy seems feasible and safe [8,15,16]. Furthermore, deprescribing of antihypertensive medication in frail older patients seems appropriate and feasible [7,17].…”
Section: Key Pointsmentioning
confidence: 99%
“…Deprescribing comprises the systematic reduction or withdrawal of medication that may cause harm or no longer contributes to an individuals' health status [13,14]. Deprescribing of glucose-lowering medication in patients with comorbidity, frailty, hypoglycemic risk, or a limited life expectancy seems feasible and safe [8,15,16]. Furthermore, deprescribing of antihypertensive medication in frail older patients seems appropriate and feasible [7,17].…”
Section: Key Pointsmentioning
confidence: 99%
“…A literature review was undertaken to analyse the treatment landscape with respect to articles addressing simplification of complex insulin regimens. The results suggested that the need to simplify treatment is mostly recognised in older individuals and those with comorbidities [24,[34][35][36][37][38][39]. Data from older populations suggest simplification of treatment can be achieved in these people with good glycaemic control.…”
Section: Current Evidence and Treatment Landscapementioning
confidence: 99%
“…In a real-world, prospective, single-arm clinical trial of older individuals with T2D, treatment simplification reduced the risk of hypoglycaemia and diabetes-related stress, without compromising glycaemic control [36]. However, little guidance and scarce data are available regarding non-elderly groups [24,[34][35][36][37][38][39].…”
Section: Current Evidence and Treatment Landscapementioning
confidence: 99%
“…There is little evidence to guide deprescribing of drugs to lower blood pressure or blood lipid levels in older patients with type 2 diabetes,15 and guidelines vary on this point. Blood pressure goals can be relaxed to <150/90 mm Hg in patients in poor health 781617.…”
Section: How To Deintensify Diabetes Carementioning
confidence: 99%
“…Decision aids and a typology classification of patients according to their attitudes towards medications and involvement in care may be useful for this purpose (box 3). 151920…”
Section: How To Conduct Conversations To Individualise Diabetes Care?mentioning
confidence: 99%